Christodoulou, Constantinos - (:unkn) unknown (My University, 2026)
Constantinos Christodoulou is a Assistant Professor with the Department of Mechanical Engineering and Materials Science and Engineering at the Cyprus University of Technology. He obtained a Higher National Diploma from Higher Technical Institute and the Engineering Council Part 2 diploma (UK) in the field of Mechanical Engineering. He received his doctoral title (PhD) from Brunel University (UK). As a member of the academic staff of the Mechanical Engineering Department in Higher Technical Institute, he was involved with the education of students in the experimental fields of Materials Technology, Production Engineering, Mechanical Engineering Principles, Mechanics of Machines and Metrology. He was also involved with the instruction of students to Computer Aided Design (AUTOCAD). He has offered more than 200 testing and consultancy services to the Cyprus Industry and Government departments related to testing of materials and calibration of instruments. His research interests are focused to the analysis and processing of vibration signals, feature extraction, development of new fault identification methods in mechanical systems, processing and testing of materials.
Keywords: Mechanical Engineering; materials; environmental; engineering